TYPHOID FEVER WITH FATAL OUTCOME IN PEOPLE WITH SEVERE TROPHOLOGICAL FAILURE IN EXTREME CONDITIONS - Yu. I. Lyashenko (Журнал инфектологии, 2018)
For purpose of clinical and morphological characterization of typhoid fever with fatal outcome was perform analysis of medical documentation as well as postmortem studies of internal tissues in 36men aged 21 to 34 years with severe body weight loss and in the conditions of combat stress in period from 1983 to 1985. The results of the study find a number of clinical and pathomorphological features of typhoid fever in patients with body weight deficiency that were in extreme conditions. Focal changes of the central nervous system were detected. The defeat of the respiratory system was characterized from the first days of the disease by bronchitis, and in the subsequent development of pneumonia, plevritis and empyema of the pleura. Majority of patients had symptoms of cardiovascular and renal failure. In died in the first week of the disease and in 2/3 parts – in a later period were combined with the symptoms of infectious-toxic encephalopathy and severe acute respiratory failure. All died had postmortem dystrophic changes of cardiomyocytes, and in patients had fatal outcome in 2–5 weeks – also focal or diffuse myocarditis. In a third of the patients who died, the disease was complicated by intestinal perforations. In a number of cases, peritonitis was a consequence of necrosis of mesenteric lymph nodes. In all patients with a fatal outcome, hemorrhagic (thrombohemorrhagic) syndrome was diagnosed. A significant proportion of patients posthumously detected signs of sepsis and other complications, many of which could be the cause of death.